Oral health topics in health sciences careers. The missing part of the body? - Bravo, Gonzalo; Salgado, Sofía; Yefi, Roger (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The topics on oral health in the academic programs of the careers of health sciences are insufficient. The purpose o this paper was to identify the topics of oral health in the academic programs of the health sciences careers of the University of Alba. A cross-sectional observational study academic programs of the health sciences careers taught by University of Alba was carried out. The topics on oral health in the academic programs of the careers of the faculty of health Sciences based on competence are scarce.